The Influence of Products, Promotions and Prices on Revisit Interests Through Visitor Satisfaction (Case Study in Jepara Ourland Park - M.Bagus Hesananta; Ag Sunarno; Supriyono (Indonesian Journal of Business Analytics, 2023)
This research is entitled The Effect of Product, Promotion and Price on Return Interest through Visitor Satisfaction (Case Study in Jepara Ourland Park). The purpose of this study was to analyze the effect of product, promotion and price on intention to return to Jepara Ourland Park with visitor satisfaction as the intervening variable. The research population is visitors to Jepara Ourland Park. Sampling taken in this study using convenience sampling as many as 160 visitors. Instrument test using validity test and reliability test. The analysis technique used the AMOS SEM (Structural Equation Modeling) Application program version 22. The results showed that product, promotion and price had a positive and significant effect on JOP visitor satisfaction. Other results show that product, promotion, price, and visitor satisfaction have an effect on the intention to return. Product, promotion and price factors have an indirect effect on the intention to return through visitor satisfaction.